2016
DOI: 10.4081/ejh.2016.2689
|View full text |Cite
|
Sign up to set email alerts
|

The injury of serotonin on intestinal epithelium cell renewal of weaned diarrhoea mice

Abstract: Diarrhoea is a common cause of death in children and weaned animals. Recent research has found that serotonin (5-HT) in the gastrointestinal tract plays an important role in regulating growth and the maintenance of mucosa, which protect against diarrhoea. To determine the influence of 5-HT on intestinal epithelium cell renewal under weaned stress diarrhoea, a weaned-stress diarrhoea mouse model was established with senna infusion (15 mL/Kg) via intragastric administration and stress restraint (SR). Mice with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 40 publications
1
9
0
1
Order By: Relevance
“…found that the intestinal and plasma 5-HT levels were higher in the stressed animals, and the elevated 5-HT level could lead to diarrhea. 5-HT and diarrhea delayed the renewal of intestinal epithelial cells and impaired the mucosal barrier and absorption ( 25 ). In autism population and their relatives, the blood 5-HT level increases, implicating the involvement of 5-HT in the pathophysiology of autism ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…found that the intestinal and plasma 5-HT levels were higher in the stressed animals, and the elevated 5-HT level could lead to diarrhea. 5-HT and diarrhea delayed the renewal of intestinal epithelial cells and impaired the mucosal barrier and absorption ( 25 ). In autism population and their relatives, the blood 5-HT level increases, implicating the involvement of 5-HT in the pathophysiology of autism ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…Since serotonin receptors have also been found to be involved in intestinal epithelial proliferation, upregulation of the receptors after PNS denervation may contribute to the recovery of cell turnover. 43,44 Changes in the specific primary neurotransmitter receptors of the denervated ANS branch are also likely to undergo changes to facilitate recovery of the intestinal epithelial turnover. PNS denervation upregulates the amount of muscarinic acetycholinergic gene expression in the stomach 45 and downregulates the expression in the small intestine 46 The intact branch of the ANS may also participate in the compensation to recover function after denervation.…”
Section: Discussionmentioning
confidence: 99%
“…VH and CD of intestinal mucosa are closely related to animal digestion. Detection of VH and CD can judge the degree of intestinal mucosal damage and the ability to repair (Dong et al, 2016). Thus, an increase in VH, V/C or decrease in the CD corresponds to an improvement in the digestion and absorption of nutrients (Hou et al, 2013).…”
Section: Discussionmentioning
confidence: 99%